Tool for extracting PP attachment disambiguation dataset - Do, Bich-Ngoc; Rehbein, Ines (Universität, 2023)
This resource contains code to extract a PP attachment disambiguation dataset as described in the paper: Do and Rehbein (2020). "Parsers Know Best: German PP Attachment Revisited". The input is in CoNLL format, and the output format is similar to the one described in de Kok et al. (2017).